A Threatened Identity: The Mental Health Status of Syrian Refugees in Egypt and Its Etiology. Issue 3 (3rd July 2017) - Kira, Ibrahim A.; Shuwiekh, Hanaa; Rice, Kenneth; Al Ibraheem, Boshra; Aljakoub, Jakoub
ABSTRACT: This study utilized the development-based trauma framework on identity traumas to study the cumulative effects of trauma on the identities of Syrian refugees. Participants included 196 Syrian refugees residing in Cairo, Egypt (Mean age = 35.99, SD  = 11.05). The rate of post-traumatic stress disorder was 33.5%, and the rate of depression was around 30%; the level of comorbidity was high with a high rate of suicidal plans or attempts (13.7%). Analyses indicated that existential annihilation anxieties, moderated by identity salience, mediated the effects of cumulative trauma on mental health. The results confirmed the utility and validity of the identity trauma model and provided evidence of the dire mental health needs of Syrian refugees.